Anisotropic modeling of structural components using embedded crystal plasticity constructive laws within finite elements. (January 2016) - Knezevic, Marko; Crapps, Justin; Beyerlein, Irene J.; Coughlin, Daniel R.; Clarke, Kester D.; McCabe, Rodney J.
Abstract: Pins are commonly used to join members of mechanical mechanisms. In order to maintain the integrity of the joint and prevent failure, there must be sufficient material of adequate strength around the pin hole to sustain the bearing and tear out loads from the pin connection. In this work, a multi-scale materials simulation model based on finite elements (FE) is developed for design and evaluation of materials for such applications. We specifically examine several constitutive models for simulating the elasto-plastic behavior of the plate material while maintaining computational efficiency. Here, models are developed for two plate materials: copper (Cu) and α-uranium (α-U), with vastly different plastic behaviors owing to their crystal structures and crystallographic textures. For Cu, digital image correlation (DIC) tests are carried out during loading of the plate/pin assembly to characterize the strain distributions in the critical hole/pin area. The corresponding FE simulations are carried out using a combination of constitutive laws involving a fine-scale polycrystal plasticity calculation, a J2 flow theory, or a combination of both. We show that the FE model using the fine-scale polycrystal plasticity constitutive law successfully captures the DIC strain fields in the hole region at different plate displacements. Surprisingly, use of the more computationally efficient J2 plasticity model also produces reasonable results in comparison with the measurements and the fine-scale constitutive law. An interesting finding is that combining fine-scale constitutive laws in the region surrounding the hole and continuum J2 theory elsewhere gives the worst agreement. It also precariously produces non-conservative estimates for the hole opening with applied displacement. These results on Cu helped subsequent simulations on α-U, where use of the fine-scale polycrystal simulation is fundamental considering the highly plastic anisotropic response of this complicated material. We demonstrate that in the α-U plates, the localized deformation in the hole region is highly dependent on the direction of displacement. Highlights: Multi-level material models are built to simulate structural parts made of Cu and α-U. DIC, mechanical testing and texture data are used to calibrate and validate the models. Anisotropy induced by microstructure and strain localizations are predicted.